2015
DOI: 10.15171/ijoem.2015.532
|View full text |Cite
|
Sign up to set email alerts
|

Persistent and Unusual Respiratory Findings after Prolonged Glutaraldehyde Exposure

Abstract: Glutaraldehyde is commonly used in endoscopy labs to clean and disinfect instruments. It can cause direct irritation of the skin and the upper and lower airways. Health care workers are also at risk for the development of irritant-induced or sensitizer-induced occupational asthma when exposed to this chemical. Herein, we report on a patient who had frequent exposures to glutaraldehyde over one year while working in an endoscopy lab and developed chronic upper and lower respiratory tract symptoms. Multiple spir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 16 publications
(23 reference statements)
0
6
0
Order By: Relevance
“…), animal handlers, woodworkers, cleaners, healthcare workers (9% of cases), those working in food processing, and so on. 2,[10][11][12] Conversely, some studies showed no increase, or even decrease, in the prevalence of respiratory allergies in farming and textile industries, consistent with the so-called 'hygiene hypothesis'. 13,14 Well-recognised high WRA risk groups are females, smokers, those with history of upper airway symptoms and bronchial hyperresponsiveness, and those with certain hereditary factors, atopic histories, and frequent exposure to high amounts of causative factors.…”
Section: Historymentioning
confidence: 88%
“…), animal handlers, woodworkers, cleaners, healthcare workers (9% of cases), those working in food processing, and so on. 2,[10][11][12] Conversely, some studies showed no increase, or even decrease, in the prevalence of respiratory allergies in farming and textile industries, consistent with the so-called 'hygiene hypothesis'. 13,14 Well-recognised high WRA risk groups are females, smokers, those with history of upper airway symptoms and bronchial hyperresponsiveness, and those with certain hereditary factors, atopic histories, and frequent exposure to high amounts of causative factors.…”
Section: Historymentioning
confidence: 88%
“…This can be explained by McCarthy [19] study who noticed that the unbalanced reduction in the FEV1 as compared to the FVC is a sign of obstructive lung diseases such as asthma, acute and chronic bronchitis, emphysema, bronchiolitis, and bronchiectasis. Also, in a case study by Copeland and Nugent they reported multiple spirometric tests during evaluation which showed variable results glutaraldehyde-induced occupational asthma including restrictive pattern and obstructive pattern [20].…”
Section: Discussionmentioning
confidence: 99%
“…Copeland and Nugent studied respiratory effects after prolonged GA exposure. 29 The results found that GA can cause both irritant-induced or sensitization-induced asthma, along with irritation of the skin and airways, and an increased immune response. The symptoms of chest tightness and persistent cough were associated with GA-induced occupational asthma.…”
Section: Review Of the Literaturementioning
confidence: 93%
“…GA use has been associated with numerous health risks, both acute and chronic, for patients and health-care workers (see Figure 1). [18][19][20][22][23][24][25][26][27]29,30,32 The new occupational exposure limit set in Japan, of less than 0.03 ppm for GA, is even lower than the limit of 0.05 ppm previously set in the United States and the UK. 32 Several studies have also demonstrated the inefficacy of GA against HPV and mycobacterium, both of which can be found on ultrasound transducers.…”
Section: Ga Usementioning
confidence: 99%